(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa - 2. La cronaca: come sono nati i protocolli - 3. Un metodo laico. The "Protocols for the resumption of religious ceremonies": the first signal of a new season in the Italian ecclesiastical politics ABSTRACT: In Italy the religions have signed with the Government some protocols for the resumption of religious ceremonies after the lockdown for the Covid-19 emergency. Those protocols are an important step in the way of an effective protection of religious freedom in a pluralistic society. The protocols inaugurate a new season in the relationships between the religions and the state in Italy.